OVERVIEW OF MEDICATION ERROR INCIDENCE IN HOSPITALS IN VARIOUS COUNTRIES: LITERATURE REVIEW - Anisa Eka Amalia; Masyitoh Basabih (Universitas Airlangga, 2023)
Background: Medication error is one of the most common types of errors contributing to patient safety incidents in hospitals. In addition to their numerous cases and high costs, medication errors also contribute to deaths in various countries. Aims: This study describes the incidence of medication errors in hospitals in various countries, determines the phase of errors that occurred the most, and describes preventive strategies for medication errors in hospitals. Methods: This study was conducted between April 2021-July 2021 using the literature review method. Data were retrieved from ProQuest, ScienceDirect, PubMed, Google Scholar, and Garuda RistekBRIN. The data are generalized and extracted in a table based on the incidence of medication errors and preventive strategies. Results: Of the eleven included studies, the incidence of medication errors in one study conducted in Nigeria was the highest (80%). Four of the eleven studies were conducted in India with varying incidence rates. Most errors occurred during the prescribing stage. The number of reports and the number of events actually have no relevance. It can be said that countries with a high number of reporting have good reporting indicators. Strategies for preventing medication errors include the implementation of an information system in the CPOE (Computerized Physician Order Entry) form and providing training for staff. Conclusion: The difference in the incidence of medication errors in developing and developed economies can be attributed to factors in the healthcare system and the lower prescribing ratio and nurse ratio in developing countries. Keywords: literature review, medication errors, patient safety